Spectroscopic study and local coordination of polyphosphate colloidal systems - Dias, F. A.; Carlos, L. D.; Messadeq, Y.; Ribeiro, SJL (Amer Chemical Soc, 2005)
The interaction between metaphosphate chains and the metal ions Ca2+ and Eu3+ has been studied in water by Eu3+ luminescence, infrared absorption, and P-31 NMR spectroscopy. Two main families of sites could be identified for the metal ions in the aqueous polyphosphate colloidal systems: (1) cagelike sites provided by the polyphosphate chain and (2) a family which arises following saturation of cagelike sites. Occupation of this second family leads to supramolecular interactions between polyphosphate chains and the consequent destabilization of the colloidal system. In the polyphosphate-Ca2+ system, this destabilization appears as a coacervation process. Equilibrium existing between colloidal species as a function of the compositions could be reasoned based on the spectroscopic measurements. The determination of coordination numbers and the correlation of the results with the observation of coacervates show that Eu3+ luminescence properties can be used to probe in a unique way the coacervation process.